2010
DOI: 10.1121/1.3484492
|View full text |Cite
|
Sign up to set email alerts
|

Bicoherence analysis of model-scale jet noise

Abstract: Bicoherence analysis has been used to characterize nonlinear effects in the propagation of noise from a model-scale, Mach-2.0, unheated jet. Nonlinear propagation effects are predominantly limited to regions near the peak directivity angle for this jet source and propagation range. The analysis also examines the practice of identifying nonlinear propagation by comparing spectra measured at two different distances and assuming far-field, linear propagation between them. This spectral comparison method can lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 13 publications
(11 reference statements)
4
20
0
Order By: Relevance
“…The calculated quadspectrum of the pressure and squared pressure reveals phase coupling between two different frequencies, which occurs from sum and difference-frequency nonlinear harmonic generation in steepening waves. 6,18 The indicator is derived from the time-domain version of the GBE for an arbitrarily diverging pressure waveform, p(t), in thermoviscous media, which may be written as…”
Section: Quantitative Nonlinearity Indicatormentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated quadspectrum of the pressure and squared pressure reveals phase coupling between two different frequencies, which occurs from sum and difference-frequency nonlinear harmonic generation in steepening waves. 6,18 The indicator is derived from the time-domain version of the GBE for an arbitrarily diverging pressure waveform, p(t), in thermoviscous media, which may be written as…”
Section: Quantitative Nonlinearity Indicatormentioning
confidence: 99%
“…Examples of nonlinearity indicators include the pressure waveform derivative skewness, 1,2 average and wave steepening factors, [3][4][5] bicoherence, 6 and the Morfey and Howell-derived Q/S.…”
Section: Introductionmentioning
confidence: 99%
“…Higher-order spectral analysis techniques, including the bispectrum 11 and quadspectrum-based indicators, 3,[12][13][14] have proven useful in nonlinearity analysis. However, because wave steepening and shock formation result in large changes in the waveform's time derivative, derivative-based measures for analysis of nonlinear propagation seem convenient.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] However, authors have disagreed on the attribution of observed phenomena to nonlinearity. Recent work by Gee et al 12,13 has examined unheated, Mach-2.0 data in the geometric near field using higher-order spectral analysis methods. Both bispectral analysis 12 and a quadspectrum indicator, 13 based on work by Morfey and Howell, 2 showed distinct evidence of quadratic phase coupling and nonlinear propagation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work by Gee et al 12,13 has examined unheated, Mach-2.0 data in the geometric near field using higher-order spectral analysis methods. Both bispectral analysis 12 and a quadspectrum indicator, 13 based on work by Morfey and Howell, 2 showed distinct evidence of quadratic phase coupling and nonlinear propagation. This Letter examines the same data set using a different analysis method-the skewness of the pressure waveform and of its time derivative-to compare with the analysis in Ref.…”
Section: Introductionmentioning
confidence: 99%